Activation of the c-myc oncogene by the immunoglobulin heavy-chain gene enhancer after multiple switch region-mediated chromosome rearrangements in a murine plasmacytoma. - Fahrlander, P D (Proc Natl Acad Sci U S A, 1985)
Presented is a detailed molecular analysis of the rearranged c-myc oncogene from ABPC45, an unusual plasmacytoma that was originally classified as translocation-negative. Previous data obtained by high-resolution chromosome banding suggested that this tumor was a member of a small group distinguished by the absence of rcpt (12;15) or (6;15) and further characterized by a band deletion near the c-myc locus on chromosome 15. However, genomic Southern blotting and analysis of the cloned oncogene in the present study reveal that (i) chromosome 12 sequences lie 365 base pairs 5' of the rearranged c-myc; (ii) this DNA consists of immunoglobulin alpha switch region and 5' immunoglobulin mu switch region sequences that are rearranged in an aberrant fashion; and (iii) the immunoglobulin heavy-chain gene enhancer element now resides approximately 2.5 kilobase pairs 5' of c-myc. We infer from these and other data that the rearrangement of c-myc in ABPC45 occurred via a multistep switch region-mediated process and that a reciprocal translocation has indeed taken place. Unlike many other plasmacytomas, this event did not interrupt the normal c-myc transcription unit. Rather, disruption of gene regulation is manifested in part by a change in relative usage of the two promoters normally used by the unrearranged gene. In contrast to several of its counterparts in Burkitt lymphomas, DNA sequence analysis of the translocated c-myc gene of ABPC45 reveals that it has not acquired point mutations in the noncoding first exon. These results strongly imply that a cis-acting regulatory element normally located 5' of exon 1 is lost and that heavy-chain constant region or enhancer sequences exert similar cis effects on translocated c-myc loci. IMAGES: